2022
DOI: 10.2337/dc21-2196
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products Predict Loss of Renal Function and High-Risk Chronic Kidney Disease in Type 2 Diabetes

Abstract: OBJECTIVE To evaluate the association of a multicomponent advanced glycation end product (AGE) panel with decline in kidney function and its utility in predicting renal function loss (RFL) when added to routine clinical measures in type 2 diabetes. RESEARCH DESIGN AND METHODS Carboxymethyl and carboxyethyl lysine and methylglyoxal, 3-deoxyglucosone, and glyoxal hydroimidazolones were measured in baseline serum and plasma samp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Although glycated hemoglobin (HbA1c), an Amadori rearrangement product formed by hemoglobin binding to glucose in red blood cells, has been demonstrated to be a reliable prognostic marker in the general diabetic population, it may not be effective in diabetes patients with chronic renal impairment [ 82 ]. Table 3 gives an overview of human studies investigating the role of AGEs and sRAGE in DN [ 6 , 34 , 35 , 36 , 83 , 84 , 85 , 86 , 87 ].…”
Section: Diabetic Nephropathymentioning
confidence: 99%
See 3 more Smart Citations
“…Although glycated hemoglobin (HbA1c), an Amadori rearrangement product formed by hemoglobin binding to glucose in red blood cells, has been demonstrated to be a reliable prognostic marker in the general diabetic population, it may not be effective in diabetes patients with chronic renal impairment [ 82 ]. Table 3 gives an overview of human studies investigating the role of AGEs and sRAGE in DN [ 6 , 34 , 35 , 36 , 83 , 84 , 85 , 86 , 87 ].…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…Even in individuals with normal kidney function (eGFR > 90 mL/min 1.73 m 2 ), there was a link between a higher AGE score and a higher likelihood of poor renal outcomes. Because they are related with two separate renal outcomes, the deterioration of both proteinuria and creatinine clearance, plasma AGEs have a wide pathophysiologic relationship with acute kidney problems [ 6 ].…”
Section: Diabetic Nephropathymentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that renal function correlates more with the degree of tubulointerstitial injury than that of the glomerular lesions in patients with DKD 1 . A large body of evidence indicates that hyperglycemia and advanced glycation end products in diabetes contribute to tubular epithelial cell injury 17 19 . Proteinuria, caused by diabetic glomerulopathy, also contributes to tubular cell injury and fibrosis development 20 .…”
Section: Er Stress-induced Tubular Injury As a Key Culprit In Aki-to-...mentioning
confidence: 99%